Organizational Contingencies Influencing the Adoption of Strategic Management Accounting Practices among Manufacturing Firms in Kenya - Kariuki, Samuel N.; Kamau, Charles Guandaru (My University, 2016)
The study sought to contend with the dearth of studies in adoption of Strategic Management Accounting (SMA) practices in manufacturing firms in Kenya with the view of filling this gap. The overall objective of the study was to investigate the organizational contingencies influencing the adoption of SMA practices among manufacturing firms in Kenya. Accordingly, the findings of the study contribute to the flourishing literature on adoption of SMA practices. This study is anchored in the framework of contingency theory to identify three contingent variables possibly displaying association with adoption of SMA. The study adopted a survey research design. The study findings indicate that the intensity of industry competition and the use of advanced manufacturing technology significantly influence the adoption of SMA among manufacturing firms in Kenya. However, the study does not find evidence to support hypothesis that life cycle stage of the firm significantly influences the adoption of SMA among manufacturing firms in Kenya. The main limitation of this study is that it focused only on three contingency variables. Future studies should explore the influence of other contingency factors on the use of SMA practices in developing countries.
Keywords: Strategic Management Accounting practices; Competitive advantage; management accounting; Manufacturing firms, competitor analysis